The Effect of Work-Life Balance on Employee Job Satisfaction with Burnout as Intervening Variable at PT xyz - Sakinah Eka Putri; A Risfan Rizaldi; Irwan Abdullah (Perpustakaan dan Penerbitan Unismuh Makassar, 2025)
This study aims to examine the effect of work–life balance on job satisfaction, with burnout serving as a mediating variable. Employing a quantitative explanatory design, the study was conducted within a mining services company in Indonesia, namely PT Pama Persada Nusantara (KPCT Site). Data were collected through a survey-based approach using structured questionnaires administered to 67 employees selected through purposive sampling. Statistical analysis was applied to test both direct and indirect relationships among the variables. The findings indicate that work–life balance has a significant positive effect on job satisfaction and a significant negative effect on burnout. However, burnout does not exhibit a significant direct effect on job satisfaction. Despite this, burnout plays an indirect mediating role in the relationship between work–life balance and job satisfaction, suggesting that improvements in work–life balance can reduce burnout levels, which in turn enhances job satisfaction indirectly. These results highlight the complexity of employee well-being dynamics, where burnout may not independently determine job satisfaction but still functions as an important psychological mechanism linking work–life balance to employee attitudes. This study contributes to the human resource management and organizational behavior literature by clarifying the mediating role of burnout in the work–life balance–job satisfaction nexus, particularly in high-demand industrial contexts. Practically, the findings underscore the importance for organizations to implement effective work–life balance policies as a strategic approach to managing employee well-being and improving job satisfaction.